Integrating a psychoeducational program with short-term therapy for Asian international college students: A randomized controlled clinical trial - Xu, Yuanruo; Wang, Han (Journal of International Students, 2025)
Mental health challenges are a significant concern for Asian international students in the U.S., who often underutilize mental health services. This study explores the effectiveness of combining psychoeducation with short-term individual therapy to improve therapy outcomes in this population. Participants (N = 44) completed pre-intervention assessments (i.e. depression, anxiety, stress, etc.) and were then randomized into two groups: psychoeducation plus therapy or therapy-only. Both groups received eight therapy sessions. Post-intervention assessments revealed that the psychoeducation plus therapy group showed significant improvements in anxiety, sleep and distress level compared to the therapy-only group. The psychoeducation group also exhibited significantly better attitudes toward mental health treatment. This study underscores the value of integrating psychoeducation with therapy to enhance mental health outcomes and attitudes among Asian international students. These findings advocate for culturally sensitive psychoeducational interventions to address the unique challenges faced by this population in university counseling settings.